ACK1 Contributes to the Pathogenesis of Inflammation and Autoimmunity by Promoting the Activation of TLR Signaling Pathways - Jing, Lina; Zhang, Xin; Liu, Dong; Yang, Yonghong; Xiong, Huabao; Dong, Guanjun (Frontiers in Immunology, 2022)
Toll-like receptors (TLRs) are the first line of defense in the immune system, whose activation plays a key role in the pathogenesis of inflammation and autoimmunity. TLRs can activate a variety of immune cells such as macrophages and dendritic cells, which produce proinflammatory cytokines, chemokines, and co-stimulatory molecules that lead to the development of inflammation and autoimmune diseases. As a nonreceptor tyrosine kinase, ACK1 is involved in multiple signaling pathways and physiological processes. However, the roles of ACK1 in the activation of TLR pathways and in the pathogenesis of inflammation and autoimmune diseases have not yet been reported. We found that the expression of ACK1 could be upregulated by TLR pathways in vivo and in vitro. Intriguingly, overexpression of ACK1 significantly promoted the activation of TLR4, TLR7, and TLR9 pathways, while knockdown of ACK1 or the use of the ACK1 inhibitor AIM-100 significantly inhibited the activation of TLR4, TLR7, and TLR9 pathways. In vivo studies showed that the inhibition of ACK1 activity by AIM-100 could significantly protect mice from the TLR4 agonist lipopolysaccharide (LPS)-mediated endotoxin shock and alleviate the condition of imiquimod-mediated lupus-prone mice and MRL/lpr mice. In summary, ACK1 participates in TLR-mediated inflammation and autoimmunity and has great potential in controlling inflammation and alleviating autoimmune diseases.